The Operation Work Evaluation and Maintenance of Serbangan Irrigation System in Rawang Panca Arga District Asahan Regency - Devi Ariyanti Manurung; Sumono Sumono; Sulastri Panggabean (Universitas Sumatera Utara, 2016)
Serbangan irrigation area is a technical irrigation area which has an area of 2.333 Ha. Evaluation of the performance of irrigation system is one way to describe the performance level of an irrigation system. This study was aimed to evaluate the performance of operation and maintenance of Serbangan irrigation system with observation or survey method. Some of the indicators used to determine the performance of the irrigation system were: functional performance and network infrastructure of irrigation, water sufficiency level, the level of accuracy of the provision of water, management of government institution, the availability of fund, human resources and farmer institutional performance. The results showed that the level of functional performance and irrigation network infrastructure was bad with the value of 2, the adequacy of water was sufficient with the value of 3, the level of accuracy was very appropriate water supply with the value of 4, the management of government institution was very good with the value of 4, the availability of funding was adequate,and human resources were not adequate each with the value of 2, the farmer institution performance was very good each with the value of 4. In general, the performance of operation and maintenance of the Serbangan irrigation system categorized good with a value of 2,98. Keywords: Irrigation system, maintenance, operation, performance, Rawang Panca Arga, Serbangan